Intravascular Papillary Endothelial Hyperplasia Associated with Venous Pool Arising in the Lower Lip: A Case Report. (22nd November 2009) - Yonezawa, Hisanobu; Hiraki, Akimitsu; Iyama, Ken-ichi; Shinohara, Masanori
Abstract : Intravascular papillary endothelial hyperplasia is a benign nonneoplastic vascular lesion that consists of endothelial cells with abundant vascular tissue with papillary proliferation. An adult female had a painless growing dark red nodule on the left side of the lower lip and often touched and gnawed at it for more than 4 years. The lesion was a tender, smooth mass approximately 1 cm in diameter without discoloration reaction. Magnetic resonance imaging of the lesion showed specific findings. She was diagnosed clinically as having mimicked hemangioma, and the lesion was totally excised under local anesthesia. Histopathological examination revealed that papillary proliferated endothelial cells with venous pool, and the lesion was diagnosed as intravascular papillary endothelial hyperplasia associated with venous pool. There has been no recurrence for more than 1 year. Despite the benign nature of this lesion, it could have been mistaken for a malignant tumor because of its clinical course and radiologic findings.